Rekonstruksi Estetika Kaligrafi Digital: Studi Adaptasi Seniman Lokal - Nurliana; Dyah Febria Wardhani (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study examines the aesthetic reconstruction of digital calligraphy as a form of adaptation by local artists to the advancement of digital technology and the dynamics of contemporary art. Digital calligraphy is not merely understood as a technical transformation of traditional practices, but as a new creative domain that facilitates the exploration of form, color, composition, and integration with modern visual media. The primary objective of this research is to identify how local artists reinterpret the aesthetic values of calligraphy through digital mediums, along with the challenges and strategies they employ in the process.The study employs a qualitative approach with a descriptive-analytical method. Data were collected through literature reviews, visual observation of digital calligraphy works, and in-depth interviews with two artists representing distinct artistic backgrounds. The findings reveal that digitalization provides expanded opportunities for visual expression, technical efficiency, and wider dissemination of artwork. However, it also presents issues related to authenticity, the perception of artistic value, and the difficulty of preserving the essence of traditional calligraphy.The study concludes that digital calligraphy is not merely a substitute for conventional techniques, but a medium that broadens aesthetic horizons through an interdisciplinary approach that combines technology, visual culture, and traditional values. Therefore, digital calligraphy artists are required to possess not only technical proficiency but also philosophical understanding to ensure their works remain authentic and meaningful in a modern context.